Utilization of Cocopeat, Empty Fruit Bunch, and Palm Kernel Shell as Renewable Energy Feedstock in Boiler - Annisa Bhikuning; Supriyadi Supriyadi; Sandi Apriandi Setiawan; Yustika Agustin; Suhaila Binti Hussain (Journal of Applied Engineering and Technological Science (JAETS), 2026)
The increasing generation of biomass waste from coconut and palm oil industries presents both environmental challenges and opportunities for renewable energy utilization. This study evaluates the potential of cocopeat, empty fruit bunch (EFB), and palm kernel shell (PKS) as alternative fuels in boiler applications through fuel characterization, blending analysis, and thermochemical performance modeling. This research aims and objective to characterize the three wastes, determine the best composition mixture as boiler fuel, and estimate the potential exhaust gas emissions. This research uses laboratory testing methods, calculation of calorific value, and estimation of exhaust gas emissions (CO₂, SO₂, NO₂) using stoichiometric calculations and steam production modeling based on energy balance principles. The test was carried out by comparing cocopeat pellets (PECO); a mixture of 50% cocopeat and 50% EFB (BCO); PKS; and EFB. The results showed that 10% PECO, 30% EFB, 60% PKS has a high calorific value of 17.05 MJ/kg. Furthermore, NO2 emissions and steam production rate are decreased to 3.42% and 7.93% than 20% PECO, 40% EFB, 40% PKS. This is due to the high value of the coconut shell fraction (PKS), which produces a high calorific value. Furthermore, the cocopeat mixture, consisting of 10%BCO, 30%EFB, and 60%PKS, has low NO2 emissions and can produce high steam in boilers. This indicates that cocopeat can be used as a new fuel when mixed with EFB, thereby maximizing the utilization of coconut waste and reducing environmental impact.